Breaking Boundaries: R.K. Narayan’s Rosie as a Trailblazer of Modern Womanhood in Indian Literature - Md. Eaqub Ali; Talukder, Md. Jobaar Talukder (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
This article delves into the multifaceted portrayal of women in R.K. Narayan’s novels, with a focus on the character Rosie as a symbol of modernity and liberation in Indian society. Narayan, known for his detailed and realistic analyses of life, presents a spectrum of women characters, ranging from traditional to liberated individuals, reflecting the societal norms and Hindu moral codes that often relegate women to a secondary position. Through an in-depth analysis of Rosie in The Guide, the article explores her journey as a modern woman challenging conventions, seeking self-identity, and confronting societal expectations. Rosie’s character becomes a lens through which the evolving roles of women in post-independence India are examined, shedding light on the nuanced interplay between tradition and modernity. The study concludes by asserting Rosie’s significance as a trailblazer, embodying the struggles and aspirations of women breaking free from historical constraints in Indian society.